Monetary Policy Analysis in Practice - Ragna Alstadheim; Ida Wolden Bache; Amund Holmsen; Junior Maih; Øistein Røisland (Norges Bank, 2010)
Norges Bank is one of few central banks publishing an interest rate fore- cast. This paper discusses how we derive and communicate the interest rate forecast. To produce the forecasts, the Bank uses a medium-sized small open economy DSGE model - NEMO. Judgments and information from other sources are added through conditional forecasting. The interest rate path is derived by minimizing a loss function representing the monetary policy mandate and the Board s policy preferences. Since optimal policy is vulnerable to model uncertainty, some weight is placed on simple interest rate rules. A weight on the deviation of the interest rate from the level implied by a simple rule is included in the loss function.
hdl:11250/2507743
Keywords: 330